FRI0541 HIGHLY ELEVATED FERRITIN LEVELS ARE ASSOCIATED WITH HAEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS/MACROPHAGE ACTIVATION SYNDROME – ARE WE MISSING TREATABLE DIAGNOSES? A RETROSPECTIVE SERVICE EVALUATION OF DIAGNOSIS IN PATIENTS WITH FERRITIN >10, 000 MICROGRAM/L. (June 2019) - Sen, Ethan; Almeida, Beverley; Moran, Louise; Foley, Charlene; Abdelrahman, Nagla; Close, Rosie; Long, Ema-Louise; Bennett, Joshua; Palman, Jason; Anderson, Catriona; Mclellan, Kirsty; Deepak, Samundeeswari; et al.
Abstract : Background: Haemophagocytic lymphohistiocytosis (HLH)/macrophage activation syndrome (MAS) is a hyperinflammatory syndrome potentially leading to critical illness. Early treatment reduces mortality but diagnosis requires a high index of suspicion. Highly elevated ferritin levels (HEF) >10, 000 μg/L are highly specific for HLH/MAS [1] and should prompt consideration of hyperinflammation. Diagnostic guidelines for HLH, requiring the presence of ≥5/8 criteria [2], and classification criteria for MAS complicating systemic juvenile idiopathic arthritis (sJIA) have been published [3]. Objectives: To assess recognition of HLH/MAS in a paediatric population with HEF. Methods: This retrospective study was conducted at 11 centres under local service evaluation permissions. Biochemistry databases identified patients ≤16 years with serum ferritin >10, 000 μg/L during a 3-year period. Each case was assessed against the 2004 HLH criteria and, for patients with sJIA, the 2016 MAS criteria. Due to limited access to some of the laboratory tests, previously-published modified HLH criteria using a threshold of ≥4/5 (excluding tissue haemophagocytosis, decreased natural killer cell function, increased soluble interleukin-2 receptor) were also applied to all patients [4]. Results: 153 patients (55.6% male) were identified. Patient diagnoses included: infections (29.4%), rheumatological (17.0%) and malignancies (17.0%). A diagnosis of HLH/MAS was made by the treating clinical team in 39.9% and considered in a further 16.3%. Using all available data, 30/153 (19.6%) met ≥5/8 criteria and 93.3% of these patients were diagnosed with HLH/MAS by the treating team. 56 (36.6%) met ≥4/5 criteria and 33 (58.9%) of these were diagnosed with HLH/MAS by clinicians. HLH/MAS was not documented as being considered in the differential in 23.2%. Of 23 patients with sJIA, 82.6% met MAS classification criteria and 89.5% of these were diagnosed with MAS by the treating clinicians. Overall mortality was 32.7% (50/153) and was 27.9% (17/61) in patients diagnosed with HLH/MAS during their admission. Conclusion: Although HEF is highly specific for HLH/MAS, the diagnosis was only made or considered in just over half of paediatric patients with this laboratory result. Increased awareness of this potentially-lethal condition is likely to lead to earlier treatment and reduced mortality. References: [1] Allen CE, et al. 2008;50:1227-35. [2] Henter JI, et al. 2007;48:124-31. [3] Ravelli A, et al. 2016;75:481-9. [4] Davì S, et al. 2014;66:2871-80. Disclosure of Interests: Ethan Sen: None declared, Beverley Almeida: None declared, Louise Moran: None declared, Charlene Foley: None declared, Nagla Abdelrahman: None declared, Rosie Close: None declared, Ema-Louise Long: None declared, Joshua Bennett: None declared, Jason Palman: None declared, Catriona Anderson: None declared, Kirsty McLellan: None declared, Samundeeswari Deepak: None declared, Kathy Gallagher: None declared, Peter Bale: None declared, Kamran Mahmood: None declared, Clare Pain: None declared, Flora McErlane: None declared, Athimalaipet Ramanan Consultant for: AbbVie, UCB, Sobi, Eli Lilly, Speakers bureau: Speaker fees/honoraria from Abbvie, SOBI, Eli Lilly and UCB, Speakers bureau: AbbVie, UCB, Sobi, Eli Lilly, Rachel Tattersall: None declared